Reimbursement for Continuous Glucose Monitoring: A European View - Heinemann, Lutz (Diabetes Technology Society, 2012)
Different systems for continuous glucose monitoring (CGM) are available on the European market. There is no unlimited reimbursement for CGM use in any European country, but in some countries, reimbursement exists for certain clinical indications. The aim of this commentary is to describe the different reimbursement situations across Europe for this innovative but costly technology, as a prelude to establishing more uniform use. From the perspective of many scientists and clinicians, a number of randomized controlled trials have demonstrated the efficacy of real-time CGM versus self-monitoring of blood glucose, at least for hemoglobin A1c reduction. Nevertheless, according to many health care professionals and potential CGM users, national health services and health insurance organizations are reluctant to reimburse CGM. Imminent technological and manufacturing developments are expected to reduce the day-to-day costs of CGM.